Monitoring Forest Cover Change of Gorumara National Park Using Landsat Data - Barman, Pritam Kumar; Wani, Afaq Majid (Indian Forester, 2024)
An important method for monitoring changes in forest cover involves combining remote sensing with geographic information systems (GIS). Using remote sensing and GiS to map forest cover is a cost-effective assessment method. This study aims to monitor and identify forest cover changes using the forest canopy density (FCD) modei in Gorumara National Parif, which spans 79.99 krtf area. Landsat 8 sateiiite imagery was used to generate FCD maps over a five-year period, from 2016 to 2021. QGiS software was used for radiometric correction, image processing and mapping. Bare son index (BSi), Advanced vegetation index (AVI) and shadow index (SI) were calculated for FCD mapping. Withan overall l(appa statistic of 0.88, the FCD classification accuracy was 91.26%. The final results Indicate that the total forested area increased by 13.25%. The areas under very dense forest (0.49 km2), moderately dense forest (0.43 km2), open forest (0.96 km2) and scrub (2.36 km2) In the non-forest category show a very low rate of deforestation.